The Analysis of Carbon Footprint in House Construction: Case Study of a 300 m2- Residence House - แสงสว่าง, ธิบดินทร์; สุขจิตร์, ทศพล; สุรโชติเวศย์, ธีระชัย (KKU Science Journal, 2014)
The research is to analyze the carbon footprint which is greenhouse gases development in the form of ton of carbondioxide equivalence and proposing the guideline for the materials selection of house construction. The case study is a 300 m2 of residence house in Ayutthaya province, Thailand. The results show that the total greenhouse gases of 241.43 ton CO2e are released from the house materials and construction activities. There are 4 resources; structure for 118.31 ton CO2e, house body for 124.12 ton CO2e, water supply and electricity installation for 0.81 ton CO2e and construction activities for 1.09 ton CO2e. The maximum greenhouse gases come from concrete. The model house is established and changed from concrete into teak. There is 104.08 ton CO2e reduced from the original house and equivalent to 5.8 Rai of teak within 10 years of CO2 absorption.